Efficient transformed ratio-type estimator using single auxiliary information - Sana Amjad; Ismail Muhammad (Kuwait Journal of Science)
This paper purposes an efficient transformed ratio-type estimator for the estimation of population variance of study variable (y) by utilizing single auxiliary information (x) under simple random sampling without-replacement. Efficiency comparison of suggested estimator has been done with some widely used existing estimators by taking real life data and simulation study. The suitability of the new estimator can be seen through empirical analysis and simulation study over the widely used existing estimators.